Iranian versus native writers’ metadiscursive hedging behavior in research article discussions in applied linguistics - Mohammad Ali Salmani Nodoushan (Studies in English Language and Education, 2026)
Metadiscursive hedging plays a vital role in shaping academic writing, particularly in research article discussions where precision and stance are crucial. Understanding how writers from different linguistic backgrounds employ hedges can reveal both cultural and disciplinary conventions that influence scholarly communication. This study addresses these issues by examining research articles with two main aims: (a) to see if Iranian and native writers’ metadiscursive hedging behavior in research articles (RA) discussions in applied linguistics differs significantly, and (b) to show if Iranian writers of RA discussions comply with, or diverge from, accepted norms of their professional community of practice. 33 RA discussions from three English-text Iranian applied-linguistics-related academic journals and 33 from native-English applied-linguistics-related academic journals published between 2009 and 2019 were randomly selected (N = 66) and analyzed in light of Hyland’s (1998) conceptual model of hedging. A counterbalanced time-series design across three trials at three-week intervals minimized carryover effects during hedge extraction, and independent-samples and one-sample t-tests were used to analyze hedge types and functions. Results revealed that native writers used significantly more hedges (M = 99.12, SD = 50.02) than Iranian writers (M = 59.84, SD = 30.33), with significant differences across all three hedging orientations, accuracy, writer- and reader-oriented, while Iranian writers also diverged markedly from professional community norms across virtually all hedging categories. These findings affirm the challenges non-native writers face in mastering academic hedging and highlight the need for metadiscourse to be more explicitly addressed in academic writing pedagogy.